Biosynthesis of silver nanoparticles using Euglena gracilis, Euglena intermedia and their extract. Issue 1 (1st February 2015) - Li, Yong; Tang, Xiaoling; Song, Wenshuang; Zhu, Lina; Liu, Xingang; Yan, Xiaomin; Jin, Chengzhi; Ren, Qingguang
Abstract : Extracellular and intracellular biosynthesis of silver nanoparticles (AgNPs) by Euglena gracilis (EG) strain and Euglena intermedia (EI) strain are reported in this study. The obtained nanoparticles showed an absorption peak approximates 420 nm in the UV–visible spectrum, corresponding to the plasmon resonance of AgNPs. According to the result of inductively coupled plasma‐atomic emission spectrometer, the intakes of silver ions by EI and EG are roughly equal. The transmission electron microscope (TEM) analysis of the successful in vivo and in vitro synthesised AgNPs indicated the sizes, ranging from 6 to 24 nm and 15 to 60 nm in diameter, respectively, and a spherical‐shaped polydispersal of the particles. The successful formation of AgNPs has been confirmed by energy dispersive X‐ray analysis connected to the TEM. The Fourier transform infrared spectroscopy measurements reveal the presence of bioactive functional groups such as amines are found to be the capping and stabilising agents of nanoparticles. To our knowledge, this is the first report where two kinds of Euglena microalga were used as the potential source for in vivo and in vitro biosynthesis of AgNPs.